2017
DOI: 10.1001/jamaoto.2017.0120
|View full text |Cite
|
Sign up to set email alerts
|

The Benefits and Limitations of Targeted Training in Flexible Transnasal Laryngoscopy Diagnosis

Abstract: Learning of flexible laryngoscopy can be improved with the use of a teaching video; however, additional interventions are needed to attain competence in accurately diagnosing upper airway lesions. Clinicians who seek to perform flexible laryngoscopy require robust training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Therefore, this result may not apply in other countries or regions with low frequencies. However, it is worth noting that there is a direct correlation between the proficiency of an intubation device and its effect in use [28]. In a national survey conducted in the United Kingdom, 91% of anesthesiology departments and 50% of intensive care units were equipped with video laryngoscopes in public hospitals; nevertheless, they were not prevalent in emergency or pediatric departments, or private hospitals [29].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, this result may not apply in other countries or regions with low frequencies. However, it is worth noting that there is a direct correlation between the proficiency of an intubation device and its effect in use [28]. In a national survey conducted in the United Kingdom, 91% of anesthesiology departments and 50% of intensive care units were equipped with video laryngoscopes in public hospitals; nevertheless, they were not prevalent in emergency or pediatric departments, or private hospitals [29].…”
Section: Discussionmentioning
confidence: 99%
“…18 For example, Russell et al showed that trainees had a better understanding of FNE after watching a narrated educational video of the procedure. 19 Considering that video-based learning can be accessed from any location, it could provide a more economical and effective method for delivering an induction programme.…”
Section: Discussionmentioning
confidence: 99%
“…Office-based flexible transnasal laryngoscopy is a common routine procedure since many years. The development of new technical equipment such as flexible high-definition endoscopes allows for very precise examination [1][2][3][4][5][6][7][8][9]. The basic principle for getting optimal magnification in laryngoscopy is to decrease the distance of the lens to the target, i.e., the nearer one gets to the vocal fold, the more details one can see.…”
Section: Discussionmentioning
confidence: 99%